S86 Serum biomarkers in SSc-ILD: association with presence, severity and prognosis. (12th November 2019) - Stock, CJW; Visca, D; DeLauretis, A; Daccord, C; Kokosi, M; Alfieri, V; Kouranos, V; Margaritopoulos, G; George, PM; Molyneaux, PL; Chua, F; Maher, TM; et al.
Abstract : Interstitial lung disease (ILD) is the main cause of death in systemic sclerosis (SSc). The progression of SSc associated ILD (SSc-ILD) is highly variable, and markers predictive of severe or progressive ILD are needed to identify patients at risk. Serum levels of 15 biomarkers were measured by Luminex assay and ELISA, as appropriate, in 189 SSc patients. Genotyping of rs2015085 in CCL18 in was carried out using a TaqMan assay in 174 patients. Statistical analysis was performed using STATA12. CCL18 and MMP-7 levels were significantly higher in patients with ILD (median: 61, 886 pg/ml and 1, 385 pg/ml, respectively) compared to patients without ILD (48, 486 pg/ml, p=0.0049 and 1, 155 pg/ml, p=0.046, respectively), and periostin levels were significantly lower in patients with ILD than without (84, 620 pg/ml compared to 105, 096 pg/ml, p=0.027). Serum levels of CCL18 (p=0.038), MMP-7 (p=0.0069), CXCL12 (p=0.016), and MMP-12 (p=0.049) were all significantly higher in patients with extensive, rather than limited, lung involvement according to the Goh et al staging (Goh et al . Am.J.Respir.Crit.Care.Med. 2008 177:1248–1254), while periostin levels were significantly lower in extensive compared to limited lung disease (p=0.025). We observed a borderline trend for a higher level of CCL18 in patients carrying the G allele of rs2015085 (65, 034 pg/ml vs 62, 541 pg/ml, p=0.05). Higher concentrations of CCL18 (p=0.001) and IL-10 (p=0.018) were associated with mortality, and neopterin was associated with time to decline in DLCO ≥15% (p=0.042). Our results suggest that CCL18, MMP-7, CXCL12, MMP-12, periostin, and neopterin may be effective biomarkers for predicting severity and or progression of lung involvement in SSc.